2012
DOI: 10.1055/s-0032-1315303
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the JAK-STAT3 Signaling Pathway by Ganoderic Acid A Enhances Chemosensitivity of HepG2 Cells to Cisplatin

Abstract: Ganoderic acid A is a lanostane triterpene isolated from Ganoderma lucidum. It has been reported to exhibit antitumor activity, which is mainly mediated through its inhibitory effect on nuclear transcription factor-kappaB and activator protein-1. But the role of ganoderic acid A in JAK-STAT3 signaling pathways is still unclear. In the present study, we investigated the effect of ganoderic acid A on the signal transducer and activator of the transcription 3 pathway and evaluated whether suppression of the signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 45 publications
0
39
0
1
Order By: Relevance
“…Ganoderic acid can also inhibit growth and angiogenesis of human breast cancer cell line MDA-MB-231 by modulating the NF-κB signaling pathway (31). On the other hand, ganoderic acid can enhance chemosensitivity of human hepatocellular carcinoma (HCC) cell line HepG2 to cisplatin by inhibiting the JAK-STAT3 signaling pathway (32). This suggests that ganoderic acid can be used in combination with chemotherapeutic agents for cancer treatment.…”
Section: Triterpenementioning
confidence: 99%
“…Ganoderic acid can also inhibit growth and angiogenesis of human breast cancer cell line MDA-MB-231 by modulating the NF-κB signaling pathway (31). On the other hand, ganoderic acid can enhance chemosensitivity of human hepatocellular carcinoma (HCC) cell line HepG2 to cisplatin by inhibiting the JAK-STAT3 signaling pathway (32). This suggests that ganoderic acid can be used in combination with chemotherapeutic agents for cancer treatment.…”
Section: Triterpenementioning
confidence: 99%
“…In a previous study, GAA was chosen as the single reference substance for multiple components determination for quantity control of GL (Da et al, 2015). GAA reportedly exhibited antinociceptive (Koyama et al, 1997), antioxidative (Zhu et al, 1999), cytotoxic (Guan et al, 2008) and hepatoprotective activities (Kim et al, 1999), especially anticancer activity (Jiang et al, 2008; Yao et al, 2012; Das et al, 2015; Radwan et al, 2015; Shao et al, 2015), which is the most attractive character of this compound.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, quantitative analysis of ganoderic acid A in G. lingzhi revealed that the pileus exhibits the highest ganoderic acid A content compared with the stipe and spore of the fruiting body; the best extraction efficiency was found when 50% ethanol was used, which suggests the use of a strong liquor to completely harness the potential of Ganoderma triterpenoids in daily life. Detection of Ganoderic Acid A in Ganoderma lingzhi by an Indirect Competitive Enzyme-Linked Immunosorbent Assay [15]. Since Ganoderma species are currently used worldwide as dietary supplements, pharmacokinetic studies of GAA after oral administration have recently received attention [16,17].…”
mentioning
confidence: 99%